The entrepreneur's playbook : more than 100 proven strategies, tips, and techniques to build a radically successful business - Green, Leonard C.; Brown, Paul B. (Gale virtual reference library., 2017)
Len Green, an experienced investor, entrepreneur, and business professor, shares inside secrets and proven tactics for launching a business. Based on his popular Ultimate Entrepreneurship course, the book explains how to: Locate sure-bet opportunities for improving products Get serious about positioning, distributing, and licensing Find funding Take calculated risks and minimize failure And much more.